BACTERIAL, VIRAL AND MUCOPLASMA PNEUMONIA IN CHILDREN (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Lung inflammation can be caused by exposure to airborne toxins or irritants, respiratory infections, and lung diseases like asthma or chronic bronchitis. Symptoms may include wheezing, shortness of breath, chest pain, and coughing. Lung inflammation can be acute (rapidly occurring and severe) or chronic (persistent or recurrent). Pneumonia is a lung infection that can make you feel sick. It happens when germs get into your lungs. Symptoms include coughing, fever and difficulty breathing.